Lysozyme quantity and quality in relation with early childhood caries: A longitudinal study - Octiara, Essie; Sutadi, Heriandi; Siregar, Yahwardiah; Primasari, Ameta (Journal of pharmacy & pharmacognosy research, 2022)
Context: Several studies have reported the relationship between lysozyme quantity (concentration) and quality (activity) with early childhood caries (ECC), but the results remain controversial. These are controversial, probably due to the cross-sectional design used in previous studies. Aims: To analyze the relation between lysozyme quantity and quality with ECC in two years old children. Methods: An observational analytic with a cohort study for nine months, with a total sample of 68 caries-free children aged 9-24 months old, selected by purposive sampling from Integrated Healthcare Center in Medan, Indonesia. The subject must have at least two primary upper incisors that have erupted. Lysozyme examination was carried out three times, at the beginning of the month, the third and the ninth month. ECC examination was assessed using the American Association of Pediatric Dentistry criteria. Lysozyme concentration was measured using a competitive ELISA method with human lysozyme C (Fine Test). Then lysozyme reading was done at an absorbance of 450 nm using a microplate reader. Lysozyme activity was assessed using the Lysozyme Detection Kit (Sigma-Aldrich and ready by spectrophotometer. Data analysis was processed with an unpaired t-test, Mann-Whitney test, and longitudinal analysis using a generalized estimating equation (linear) test with a significant value, p<0.05. Results: This showed that there was not any relationship found between lysozyme concentration and ECC (p>0.05). However, there was a relationship between lysozyme activity and ECC (p=o.oo8). Conclusions: ECC children had higher lysozyme activity when compared to caries-free children.